The Ethics of Access: Who Is Offered a Cesarean Delivery, and Why?. Issue 6 (28th July 2015) - Ralston, Steven J.; Farrell, Ruth M.
Abstract: Much of the discourse in the bioethics literature on what is often called "cesarean delivery on maternal request" has focused on balancing respect for patient autonomy with attention to the short‐ and long‐term risks of this procedure to maternal and neonatal well‐being. And while there has been some analysis of the social and economic costs inherent in performing cesareans, much of the clinical and ethical analysis has concluded that, given the degree of risk to the mother and neonate from a primary or single repeat cesarean delivery, there is sufficient justification for pregnant women to request and obtain this procedure from obstetricians willing to meet such requests. However, these same analyses often caution that physicians should not offer these elective cesareans to all women, but only to those who initiate the request. This paper analyzes recommendations that do not promote universal access to these procedures and concludes that such a policy is ethically unjustifiable, as it treats women who do not inquire about such procedures differently. Depriving appropriate candidates—for example, healthy women who are good surgical candidates and desire only or two children—of information about elective cesarean delivery is a form of undue influence on women's decision‐making. .